Reviews (Studies in 20th & 21st Century Literature, 2014)
Michael Issacharoff. Discourse as Performance. Stanford: Stanford University Press, 1989. vii + 161 pp. Reviewed by Gerald Prince, University of Pennsylvania Thomas M. Kavanagh, ed. The Limits of Theory. Stanford: Stanford University Press, 1989. 254 pp. Reviewed by André J.M. Prévos, Pennsylvania State University, Worthington Scranton Campus Wendy B. Faris. Labyrinths of Language: Symbolic Landscape and Narrative Design in Modern Fiction. Baltimore and London: The Johns Hopkins Press, 1988. 242 pp. Reviewed by Carol Rigolot, Princeton University Eve Tavor Bannet. Structuralism and the Logic of Dissent: Barthes, Derrida, Foucault, Lacan. Urbana and Chicago: University of Illinois Press, 1989. 299 pp. Reviewed by Andrew J. McKenna, Loyoyla University of Chicago Gary Saul Morson and Caryl Emerson, eds. Rethinking Bakhtin: Extensions and Challenges. Evanston: Northwestern University Press, 1989. Reviewed by Lewis Bagby, University of Wyoming Fernando Moreno. Carlos Fuentes. La mort d'Artemio Cruz: entre le mythe et l'histoire. Paris: Editions Caribeennes, 1989. Reviewed by Susan Levine, Lawrence, Kansas
Keywords: Michael Issacharoff; Discourse as Performance; Thomas M. Kavanagh; The Limits of Theory; Wendy B. Faris; Labyrinths of Language: Symbolic Landscape and Narrative Design in Modern Fiction; Eve Tavor Bannet; Structuralism and the Logic of Dissent: Barthes Derrida Foucault Lacan; Gary Saul Morson; Caryl Emerson; Rethinking Bakhtin: Extensions and Challenges; Fernando Moreno; Carlos Fuentes. La mort d' Artemio Cruz: entre le mythe et l' histoire; Gerald Prince; André J.M. Prévos; Carol Rigolot; Andrew J. McKenna; Lewis Bagby; Susan Levine